Fully degradable triboelectric nanogenerator using graphene composite paper to replace copper electrodes for higher output performance. (April 2023) - Liu, Hanbin; Shu, Qinsi; Xiang, Huacui; Wu, Haiwei; Li, Zhijian; Zhou, Hongwei
Abstract: Given the global environmental crisis caused by electronic waste (e-waste), the development of the triboelectric nanogenerators (TENGs) using sustainable materials have attracted great interests, however, their preparation still remains a challenge. In this work, we proposed a fully degradable triboelectric nanogenerator (FD-TENG) with recycled cellulose (RC) as positive friction layer, poly (butylene adipate-co-terephthalate) (PBAT) as negative friction layers and using graphene composite paper (GC-paper) as electrodes instead of copper. For the first time, we found the microstructure on the surface of the GC-paper may transfer to the frication layer under pressure and improve the output performance. The FD-TENG gained the open-circuit voltage of 100 V, short-circuit current of 7 µA and power density of 637 mW m −2 under a pressure of 50 kPa with device size of 2 × 2 cm 2, which was respectively about 2.22, 3.04 and 5.05 times comparing with that using copper as electrodes. It was capable of lighting up at least 41 light-emitting diodes (LEDs), charging up different electronic devices, monitoring the human motions and working as a doorbell or burglar alarm. Interestingly, the FD-TENG can be totally degraded in soil after three months being free of e-waste accumulation. In addition, the output performance of the FD-TENG can be improved by chemically modification of 3-aminopropyl triethoxysilane (APTES), which achieved output voltage up to 160 V, current of 10.6 µA, and power density of 1365 mW m −2 and quickly charged a 220 µF capacitor to 2 V within 30 s. This kind of FD-TENG may pave a way for the development of novel sustainable electronics, and the strategy of the electrode with microstructures may provide reference for the development of high performance self-powered flexible devices. Graphical Abstract: ga1 Highlights: Fully degradable (FD) TENG shown higher output performance than previous reports. Graphene-paper as electrodes increased the output performance at least 2.22 times. High output performance relates with the microstructures on electrode. FD-TENG worked well for energy harvesting and wireless sensing. The main components can be degraded in soil and not affect the plant germination.